Effects of suppressing bioavailability of insulin‐like growth factor on age‐associated intervertebral disc degeneration. Issue 4 (27th July 2020) - Kritschil, Rebecca; Zhang, Zhongying; Lei, Changbin; Zhong, Jiongbiao; Dong, Qing; Lee, Joon; Conover, Cheryl A.; Sowa, Gwendolyn; Vallejo, Abbe N.; Vo, Nam
Abstract: Suppression of the insulin‐like growth factor‐1 (IGF‐1) signaling pathway reduces age‐related disorders and increases lifespan across species, making the IGF‐1 pathway a key regulator of aging. Previous in vitro intervertebral disc cell studies have reported the pro‐anabolic effect of exogenously adding IGF‐1 on matrix production. However, the overall effects of suppressing IGF‐1 signaling on age‐related intervertebral disc degeneration (IDD) is not known. Here, the effects of suppressing IGF‐1 signaling on age‐related IDD in vivo were examined using PAPPA −/− mice. These are animals with targeted deletion of pregnancy‐associated plasma protein A (PAPPA), the major protease that cleaves inhibitory IGF binding proteins that control bioavailability of IGF‐1 for cell signaling. Compared to age‐matched wild‐type (Wt) littermates, reduced levels of matrix proteoglycan (PG) and aggrecan were seen in discs of 23‐month old PAPPA −/− mice. Decreased aggrecanolysis and expression of two key catabolic markers, matrix metalloproteinase‐3 and a disintegrin and metalloproteinase with thrombospondin motifs‐4, were also observed in discs of old PAPPA −/− mice compared to Wt littermates. Suppressing IGF‐1 signaling has been implicated to shift cellular metabolism toward maintenance rather than growth and decreasing cellular senescence. Along this line, discs of old PAPPA −/− mice also exhibited lower cellular senescence, assessed by p53 and lamin B1 markers. Collectively, the data reveal complex regulation of disc matrix homeostasis by PAPPA/IGF‐1 signaling during chronologic aging, that is, reduced IGF‐1 bioavailability confers the benefit of decreasing disc cellular senescence and matrix catabolism but also the disadvantage of decreasing disc PG matrix anabolism. This pathway requires further mechanistic elucidation before IGF‐1 could be considered as a therapeutic growth factor for treating IDD. Abstract :